UPAYA MENEKAN PERILAKU FANDALISME SISWA DI LEMBAGA PENDIDIKAN ISLAM (Studi Kasus di MTs Negeri Kadur Pamekasan) - Mohammad Thoha (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
One of the factors making students’ failure in learning is students’ vandalism either inside or outside the class. In facing this case, teachers and organizer of institution need certain wise approach. This article focuses on, first, how are the students vandalism images at MTs Negeri Kadur Pamekasan, and second, what are the efforts to push down the students vandalism images at MTs Negeri Kadur Pamekasan. The results showed that the images of students’ vandalism at MTs Negeri Kadur Pamekasan were: coming late into the class, not wearing uniform, not attending the class, not doing the homework, going out with close friend, being lazy in studying, smoking, colouring the hair, bringing mobile phone, going out of the school without permission, stealing and wearing earrings. The efforts done are using moral and emotional approach and spiritual approach.